2022
DOI: 10.1007/s10238-022-00793-5
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on exosomal proteins as diagnostic markers of gastric cancer (review article)

Abstract: Gastric cancer (GC) is one of the most common types of tumors and the most common cause of cancer mortality worldwide. The diagnosis of GC is critical to its prevention and treatment. Available tumor markers are the crucial step for GC diagnosis. Recent studies have shown that proteins in exosomes are potential diagnostic and prognostic markers for GC. Exosomes, secreted by cells, are cup-shaped with a diameter of 30–150 nm under the electron microscope. They are also surrounded by lipid bilayers and are widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 179 publications
0
8
0
Order By: Relevance
“…TGF-β1 is an immunosuppressive cytokine that has been detected in exosomes of GC patients and was found to be correlated with lymphatic metastasis [ 52 , 53 ]. Tripartite motif 3 (TRIM3) is a protein that normally inhibits the proliferation of GC cells; it has been found that the levels of TRIM3 in serum exosomes of patients with GC are lower than those of healthy controls, making it a potential diagnostic biomarker for GC [ 54 ]. Gastrokine-1 (GKN-1) is another exosomal cargo protein involved in regulating the immune response and inhibiting proliferation of GC cells [ 54 ].…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…TGF-β1 is an immunosuppressive cytokine that has been detected in exosomes of GC patients and was found to be correlated with lymphatic metastasis [ 52 , 53 ]. Tripartite motif 3 (TRIM3) is a protein that normally inhibits the proliferation of GC cells; it has been found that the levels of TRIM3 in serum exosomes of patients with GC are lower than those of healthy controls, making it a potential diagnostic biomarker for GC [ 54 ]. Gastrokine-1 (GKN-1) is another exosomal cargo protein involved in regulating the immune response and inhibiting proliferation of GC cells [ 54 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Tripartite motif 3 (TRIM3) is a protein that normally inhibits the proliferation of GC cells; it has been found that the levels of TRIM3 in serum exosomes of patients with GC are lower than those of healthy controls, making it a potential diagnostic biomarker for GC [ 54 ]. Gastrokine-1 (GKN-1) is another exosomal cargo protein involved in regulating the immune response and inhibiting proliferation of GC cells [ 54 ]. Yoon et al found that healthy controls had significantly higher serum GKN1 levels than GC patients (6.34 ng/μL vs. 3.48 ng/μL, p < 0.0001), suggesting it to be another potential biomarker for GC.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The c‐Met kinase belongs to the receptor tyrosine kinase (RTK) family and is expressed primarily on the surfaces of various epithelial cells 1 . Aberrant expression of c‐Met has been found in gastric cancer (GC) in multiple clinical and preclinical studies, making it a key cancer biomarker 2–3 . Abnormal amplification, deregulation, and genetic mutations in the MET encoder gene have also been reported to cause the overexpression of c‐Met 4 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Aberrant expression of c-Met has been found in gastric cancer (GC) in multiple clinical and preclinical studies, making it a key cancer biomarker. [2][3] Abnormal amplification, deregulation, and genetic mutations in the MET encoder gene have also been reported to cause the overexpression of c-Met. 4 Structurally, c-Met is a 1390 amino acid long-chain protein and is a heterodimer of an extracellular chain α, linked to a transmembrane chain β with a single disulfide bridge.…”
Section: Introductionmentioning
confidence: 99%